PENGARUH SPIRITUAL LEADERSHIP DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA KARYAWAN CV.SINAR DAYA ALAM (SDA) - Ferdiansah Dwi Prasojo; Ratnawili Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the Influence of Spiritual Leadership and Intellectual Intelligence on CV. Sinar Daya Alam (SDA). This type of research is a type of quantitative descriptive research, The population of this study is CV. Sinar Daya Alam (SDA) as the object of research. The data collection techniques used were observation, interviews, and questionnaires. Meanwhile, the data analysis technique uses descriptive analysis, inferential analysis using SPSS and determination coefficient analysis (R2). The results of this study show that Spiritual Leadership has a positive and significant effect on Employee Performance. This means that the better the level of Spiritual Leadership the more it will increase the formation of employee performance. Intellectual Intelligence has a positive effect on Employee Performance but is not significant. The better the Intellectual Intelligence more positive it will be on Employee Performance. Spiritual Leadership and Intellectual Maturity together have a positive and significant effect on CV. Sinar Daya Alam (SDA). This is if the level of Spiritual Leadership and Intellectual Intelligence is high, it will improve the performance of employees in the company. Keywords : Spiritual Leadership, Intellectual Intelligence, Employee Performance.